Tdap vaccination during pregnancy interrupts a twenty-year increase in the incidence of pertussis. Issue 12 (10th March 2020) - Langsam, Dean; Anis, Emilia; Haas, Eric J.; Gosinov, Ruslan; Yechezkel, Matan; Grotto, Itamar; Shmueli, Erez; Yamin, Dan
Highlights: We modeled pertussis incidence in Israel between 1998 and 2019. Our model identified a 4-year periodicity and a 325% increase in incidence between 2002 and 2014. We observed a 59.7% decline from 2015 to 2019 compared to the model's projection. A sharper reduction of 71.2% was observed in infants of age two months and below. This decline is partly attributable to the introduction of maternal Tdap vaccination. Tdap vaccination during pregnancy is a promising tool towards controlling pertussis. Abstract: Pertussis incidence in developed countries, including Israel, has increased over the past two decades despite the addition of two booster doses in children. However, as pertussis is characterized by a multi-annual periodicity, and since clinical diagnosis can miss cases, determining disease trends at the population level is challenging. To bridge this gap, we developed a simple statistical model to capture the temporal patterns of pertussis incidence in Israel. Our model was calibrated and tested using laboratory-confirmed cases of pertussis for the Israeli population between 1998 and 2019. The model identifies a clear four-year periodicity of pertussis incidence over the past two decades that is identical to the one observed in the pre-vaccine era. Accounting for this periodicity, the model shows a 325% increase in pertussis incidence from 2002 to 2014. These multi-year trends were interrupted shortly after the introduction of routine immunization of Tdap vaccine in pregnancy in 2015, after which we found a 59.7% (95% CI: 57.7–61.6%) decline in pertussis incidence and a 49.5% (36.0–61.6%) decline in hospitalizations compared to the model's projection. While this sharp decline cannot be fully attributed to the newly introduced vaccination policy, sharper reductions of 71.2% (65.6–76.1%) in incidence and 58.4% (39.6–72.7%) in hospitalizations, have been observed in infants of age two months and below - young infants that have yet to become vaccinated and are more likely to be protected by maternal vaccination. Our work suggests that Tdap vaccination during pregnancy is a promising policy for controlling pertussis. Furthermore, due to the stable periodicity of pertussis, public health decision-makers should invest continuous efforts in the implementation of this strategy with additional reinforcement in expected peak years.